Administrasi Keimigrasian di Indonesia: Tantangan dan Prospek dalam Era Globalisasi - Muhammad Rifky Satriawan; Mas Budi Priyatno; Habbi Firlana (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study examines the dynamics of immigration administration in Indonesia, amidst the increasing mobility of people across borders due to globalization. This situation positions immigration administration as a strategic instrument for public service and safeguarding national sovereignty. The purpose of this study is to describe immigration administration regulations, analyze the challenges faced in their implementation, and identify prospects for their future development. This study uses qualitative methods with a literature review approach and normative analysis. Research data are sourced from primary legal sources, such as Law Number 6 of 2011, which was amended by Law Number 63 of 2024, as well as secondary legal sources such as journal articles and official reports. The results show that Indonesia has implemented reforms through regulatory updates and the digitalization of services such as e-visas and the Immigration Management Information System SIMKIM. However, challenges remain, including suboptimal inter-agency coordination, limited human resources, and gaps between regulations and practice. Future prospects focus on strengthening transparent governance, developing an integrated digital system, and increasing the capacity of immigration officials to address global dynamics.